2020
DOI: 10.1016/j.jdin.2020.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The tumor genetics of acral melanoma: What should a dermatologist know?

Abstract: Dermatologists stand at the gateway of individualization of classification, treatment, and outcomes of acral melanoma patients. The acral melanoma genetic landscape differs in vital ways from that of other cutaneous melanomas. These differences have important implications in understanding pathogenesis, treatment, and prognosis. The selection of molecularly targeted therapy must be adapted for acral melanoma. It is also critical to recognize that tumor development is far more complex than an isolated event, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 106 publications
0
18
0
1
Order By: Relevance
“…Acral melanoma has been frequently associated with poorer outcome than other melanoma subtypes [ 11 ]. The genetic landscapes of acral melanoma are strikingly different from other sun damage-associated melanoma by showing lower mutational loads, more chromosomal structural changes, and lower levels of cytosine to thymine mutations [ 12 ]. Although mutation signatures contribute to the clinical course and treatment response, relatively poorer outcome of acral melanoma is associated with the delayed presentation at diagnosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acral melanoma has been frequently associated with poorer outcome than other melanoma subtypes [ 11 ]. The genetic landscapes of acral melanoma are strikingly different from other sun damage-associated melanoma by showing lower mutational loads, more chromosomal structural changes, and lower levels of cytosine to thymine mutations [ 12 ]. Although mutation signatures contribute to the clinical course and treatment response, relatively poorer outcome of acral melanoma is associated with the delayed presentation at diagnosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…As acral melanomas develop in sun-shielded areas of the body, they are not believed to be caused by exposure to ultraviolet (UV) radiation. Hence, oncogenic pathway activation in acral melanoma is UV-independent, in contrast to the induction of oncogenic circuits in cutaneous melanomas (42,43). Wholeexome and whole-genome sequencing studies revealed that, compared with cutaneous melanomas, acral melanomas have fewer single nucleotide polymorphisms (SNPs) and indel mutations and a higher number of structural rearrangements and focal chromosomal copy number aberrations (44).…”
Section: Mutational Landscapementioning
confidence: 99%
“…The efficacy of targeted therapies has also been assessed in patients with acral melanoma. Aberrations in MAPK, PI3K/ AKT/PTEN, TERT, WNT, and CDK4/CDKN2A signaling pathways are frequent in acral melanoma (43). However, despite the fact that acral melanomas have potentially actionable targets (45), a limited number of targeted therapies are available for the treatment of patients with acral melanoma.…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…Berdasarkan biologi molecular acral melanoma sebagian besar disebabkan delesi atau amplifikasi KIT pada exon 9, 11, 13, 17 dan 18 sedikit berbeda dengan melanoma pada regio kepala dan leher yang sebagian besar disebabkan mutasi pada gen BRAF. 28,17 Pada penelitian ini didapatkan tipe histopatologi yang paling banyak pada nevus melanositik adalah dermal naevus (55,9%) sesuai dengan penelitian Damsky dkk yang menyatakan dermal naevus merupakan tipe histopatologi yang paling sering. 3 Menurut konseps klasik nevus melanositik, junctional, compound, dan dermal naevus merupakan tahapan yang berbeda dari urutan patogenetik ("Abtropfung").…”
Section: Pembahasanunclassified